2016
DOI: 10.1021/acs.est.5b05060
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Lead Release to Potable Water

Abstract: The influence of temperature on the solubility of representative lead solids present in drinking-water systems and the lead release to potable water was examined. Temperature had surprisingly little effect on the dissolution of cerrusite, hydrocerussite, chloropyromorphite, lead orthophosphate, and lead oxide solids; however, in the presence of natural organic matter, lead oxide dissolution was 36 times greater (36 versus 1277 ppb) at 20 °C compared to 4 °C due to accelerated reductive dissolution. The solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 55 publications
3
48
0
1
Order By: Relevance
“…Overall, these results are in agreement with a recent study in Canada that identified up to a 6-10.6 µg/L difference between winter and summer lead concentrations in tap water, depending on how the sample was taken (flushed or stagnant) (Ngueta et al, 2014). Experiments involving a full scale pipe rig utilising 'harvested' pipes from Washington and Providence RI, demonstrated the relationship between temperature and lead release from pipes (Masters et al, 2016). There was a correlation of r=0.73 for particulate lead and r=0.70 for dissolved lead, resulting in average particulate lead levels that were six times higher in summer than in winter, and average dissolved lead levels three times higher.…”
Section: Lead In Tap Water Samplessupporting
confidence: 91%
“…Overall, these results are in agreement with a recent study in Canada that identified up to a 6-10.6 µg/L difference between winter and summer lead concentrations in tap water, depending on how the sample was taken (flushed or stagnant) (Ngueta et al, 2014). Experiments involving a full scale pipe rig utilising 'harvested' pipes from Washington and Providence RI, demonstrated the relationship between temperature and lead release from pipes (Masters et al, 2016). There was a correlation of r=0.73 for particulate lead and r=0.70 for dissolved lead, resulting in average particulate lead levels that were six times higher in summer than in winter, and average dissolved lead levels three times higher.…”
Section: Lead In Tap Water Samplessupporting
confidence: 91%
“…Alternative choices in complex formation constants primarily impacted the predicted dissolved lead levels resulting from equilibrium with a given solid phase. Research by Masters, Welter, and Edwards () verified that lead levels in water can vary based on the lead phases present and the temperature. However, temperature was set to 25°C because no temperature adjustment functions were available for virtually all of the aqueous species or solid phases important to the lead solubility computation.…”
Section: Methodsmentioning
confidence: 99%
“…According to Peng et al (2012), As, V and U released from mineral deposits dissolution were more prevalent in GW supplies, since they could not be efficiently removed by traditional water treatment plants. Some other metal ions such as Pb, Cu, Cd, Cr and other impurities might originate from pipe materials and pipe joints in DWDS (Masters et al, 2016). We studied the effects of sulfate on seven heavy metals (including As, Cr, Cu, Mn, Ni, Pb and Zn) release using cast iron pipe-loops with different corrosion scales.…”
Section: Heavy Metal Releasementioning
confidence: 99%